2022
DOI: 10.1007/s10741-022-10237-7
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid seeding as a disease mechanism and treatment target in transthyretin cardiac amyloidosis

Abstract: Transthyretin (TTR) is a tetrameric transport protein mainly synthesized by the liver and choroid plexus. ATTR amyloidosis is characterized by the misfolding of TTR monomers and their accumulation within tissues as amyloid fibres. Current therapeutic options rely on the blockade of TTR production, TTR stabilization to maintain the native structure of TTR, amyloid degradation, or induction of amyloid removal from tissues. “Amyloid seeds” are defined as small fibril fragments that induce amyloid precursors to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Notably, the addition of preformed seeds can significantly shorten or even complete this phase (seeding phenomenon). 13 Later, in the elongation phase, the addition of monomers to the nucleus results in formation of amyloid fibrils. These fibrils can be composed of a mixture of both C terminal fragments and full-length TTR (type A fibrils) or by full-length TTR only (type B fibrils).…”
Section: Pathogenesismentioning
confidence: 99%
“…Notably, the addition of preformed seeds can significantly shorten or even complete this phase (seeding phenomenon). 13 Later, in the elongation phase, the addition of monomers to the nucleus results in formation of amyloid fibrils. These fibrils can be composed of a mixture of both C terminal fragments and full-length TTR (type A fibrils) or by full-length TTR only (type B fibrils).…”
Section: Pathogenesismentioning
confidence: 99%
“…The need for early diagnosis of CA and accurate amyloid typing is raising new problems and challenges for both physicians and pathologists [ 80 , 81 , 82 ]. The presence of a dual pathology, i.e., ATTR and AL amyloidosis developing subsequently in the same patient and affecting the heart, has been demonstrated in anecdotic cases, but the advancement in diagnostic tools will likely disclose more of these forms, which will then raise relevant issues for treatment strategies [ 15 , 56 , 83 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Many in vitro studies investigated the process leading to the metamorphosis of TTR from the globular (physiological) to the fibrils (pathological) structure [ 165 ]. All these studies focused on how TTR tetramers are modified, but the role of RBP or T4 in preserving TTR function in vivo was scarcely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the ratio of wt-to-variant TTR shifted towards a greater contribution to the first [ 164 ]. This data suggested that remnant amyloid deposits of TTRv could represent a focal point for the deposition of the wild-type TTR (amyloid seeding) [ 165 ], furthermore showed that amyloid deposits underwent a turnover likely driven by dynamic processes of amyloid fibril formation and catabolism in the ECM.…”
Section: Ttr Catabolismmentioning
confidence: 99%